Civil Rights and the Environment in African-American Literature, 1895-1941 - John Claborn (Environmental Cultures, 2017)
Explores how African-American writers in the early 20th century - including Booker T. Washington, W.E.B. Dubois and Effie Lee Newsome - grappled with environmental crisis in the context of the civil rights movement.